Socioeconomic inequalities in informal payments for health care: An assessment of the ‘Robin Hood’ hypothesis in 33 African countries - (:unkn) unknown (My University, 2016)
In almost all African countries, informal payments are frequently made when accessing health care. Some literature suggests that the informal payment system could lead to quasi-redistribution among patients, with physicians playing a ‘Robin Hood’ role, subsidizing the poor at the expense of the rich. We empirically tested this assumption with data from the rounds 3 and 5 of the Afrobarometer surveys conducted in 18 and 33 African countries respectively, from 2005 to 2006 for round 3 and from 2011 to 2013 for round 5. In these surveys, nationally representative samples of people aged 18 years or more were randomly selected in each country, with sizes varying between 1048 and 2400 for round 3 and between 1190 and 2407 for round 5. We used the ‘normalized’ concentration index, the poor/rich gap and the odds ratio to assess the level of inequality in the payment of bribes to access care at the local public health facility and implemented two decomposition techniques to identify the contributors to the observed inequalities. We obtained that: i) the socioeconomic gradient in informal payments is in favor of the rich in almost all countries, indicating a rather regressive system; ii) this is mainly due to the socioeconomic disadvantage itself, to poor/rich differences in supply side factors like lack of medicines, absence of doctors and long waiting times, as well as regional disparities. Although essentially empirical, the paper highlights the need for African health systems to undergo substantial country-specific reforms in order to better protect the worse-off from financial risk when they seek care.
Keywords: African Research